2016
DOI: 10.1186/s12903-015-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral photobiomodulation-induced orthodontic tooth alignment: a preliminary study

Abstract: BackgroundNumerous strategies have been proposed to decrease orthodontic treatment time. Photobiomodulation (PBM) has previously been demonstrated to assist in this objective. The aim of this study was to test if intraoral PBM increases the rate of tooth alignment and reduces the time required to resolve anterior dental crowding.MethodsNineteen orthodontic subjects with Class I or Class II malocclusion and Little’s Irregularity Index (LII) ≥ 3 mm were selected from a pool of applicants, providing 28 total arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 51 publications
1
49
1
1
Order By: Relevance
“…It is hoped that this newer intraoral device may be subject to future well-designed and constructed clinical trials. 58…”
Section: Pbmt: Accelerated Otmmentioning
confidence: 99%
“…It is hoped that this newer intraoral device may be subject to future well-designed and constructed clinical trials. 58…”
Section: Pbmt: Accelerated Otmmentioning
confidence: 99%
“…The increased demand for rapid orthodontic treatment has led to the introduction of several methods, which also reduce potential risks of dental and periodontal complications such as external apical root resorption, high levels of dental caries, and subsequent gingivitis and periodontitis [3][4][5]. Some of the proposed methods are adequate use of brackets, controlling force levels, and relying on less friction bracket systems, photobiomodulation, pharmacological approaches, or low-intensity laser irradiation [6][7][8][9][10][11]. However, irrespective of the method, the rate of the tooth movement is dictated by the biologic response to the applied orthodontic forces [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding PBM is limited to one trial using the OrthoPulse™ appliance which was conducted by a consulting orthodontist for the company (Biolux Research Ltd.). The study concluded that intraoral PBM increased the average rate of tooth movement resulting in a 54 per cent average decrease in alignment duration compared with a control . However, there were confounding variables including the use of different brackets in the two test groups.…”
Section: Non‐surgical Methodsmentioning
confidence: 95%